2017
DOI: 10.1021/acsami.6b14372
|View full text |Cite
|
Sign up to set email alerts
|

Robust Interfacial Exchange Bias and Metal–Insulator Transition Influenced by the LaNiO3 Layer Thickness in La0.7Sr0.3MnO3/LaNiO3 Superlattices

Abstract: Artificial heterostructures based on LaNiO (LNO) have been widely investigated with the aim to realize the insulating antiferromagnetic state of LNO. In this work, we grew [(LaSrMnO)-(LaNiO)] superlattices on (001)-oriented SrTiO substrates by pulsed laser deposition and observed an unexpected exchange bias effect in field-cooled hysteresis loops. Through X-ray absorption spectroscopy and magnetic circular dichroism experiments, we found that the charge transfer at the interfacial Mn and Ni ions can induce a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…The peak at 533 eV is distinctly visible in all SLs, and its intensity is larger in the (001)-oriented SL, indicating the higher degree of hybridization between Mn and Ni ions. As the Fermi level of LMO is higher than that of LNO layer, the presence of electron transfer from Mn to Ni sites is in good agreement with the results of Mn L -edge and O K -edge spectra 13 . Therefore, it is plausible to consider the charge transfer occurring from interfacial Mn to Ni ions in SLs.
Figure 4Normalized XAS spectra at the ( a ) Mn L -edge and ( b ) O K -edge from different samples recorded in TEY mode at room temperature.
…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The peak at 533 eV is distinctly visible in all SLs, and its intensity is larger in the (001)-oriented SL, indicating the higher degree of hybridization between Mn and Ni ions. As the Fermi level of LMO is higher than that of LNO layer, the presence of electron transfer from Mn to Ni sites is in good agreement with the results of Mn L -edge and O K -edge spectra 13 . Therefore, it is plausible to consider the charge transfer occurring from interfacial Mn to Ni ions in SLs.
Figure 4Normalized XAS spectra at the ( a ) Mn L -edge and ( b ) O K -edge from different samples recorded in TEY mode at room temperature.
…”
Section: Resultssupporting
confidence: 85%
“…However, Zhou et al . have recently observed exchange bias in the relatively thin layer in (001) stacking of LMO/LNO SLs and found that thicker SLs exhibit lower charge transfer rates compared to thinner SLs 13 . Inspired by these findings, we chose the thin SLs as (3–3) 10 in (001) plane, (4–4) 10 in (110) plane, and (5–5) 10 in (111) plane for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is obvious that H EB decreases rapidly with increasing temperature, finally vanishes at the blocking temperature ( T B ) of 120 K. As T B gets smaller than the freezing temperature T F of the spin glass, we suggest that the exchange bias effect in the LSMO/LNO interface is supported by the emergence of the spin glass state. As previously reported, in a range of diverse materials such as LSMO/SMO, the existence of the spin glass state is known to lead an exponential temperature dependent decay of H EB and H C [29, 3335]. In Fig.…”
Section: Resultsmentioning
confidence: 73%
“…The electronic structure at the perovskite-oxide interface between two transition metal oxides features complex interactions among the lattice, charge, spin, and orbital degrees of freedom and shows many emergent physical properties, including high-temperature superconductivity [1], magnetoresistance [2], exchange bias (EB) [3], and ferroelectricity [4]. With regard to these complex oxide structures, many of which are epitaxially compatible, the past decade has seen rapid growth in materials science at the atomic level with the creation of heterostructures with unique properties [5].…”
Section: Introductionmentioning
confidence: 99%